Age-dependent relevance of endogenous 5-lipoxygenase derivatives in anxiety-like behavior in mice. - Luciana M Leo; Suellen Almeida-Corrêa; Claudio A Canetti; Olavo B Amaral; Fernando A Bozza; Fabricio A Pamplona (PLoS ONE, 2014)
When 5-lipoxygenase (5-LO) is inhibited, roughly half of the CNS effect of the prototypic endocannabinoid anandamide (AEA) is lost. Therefore, we decided to investigate whether inhibiting this enzyme would influence physiological functions classically described as being under control of the endocannabinoid system. Although 5-LO inhibition by MK-886 reduced lipoxin A4 levels in the brain, no effect was found in the elevated plus maze (EPM), even at the highest possible doses, via i.p. (10 mg/kg,) or i.c.v. (500 pmol/2 µl) routes. Accordingly, no alterations in anxiety-like behavior in the EPM test were observed in 5-LO KO mice. Interestingly, aged mice, which show reduced circulating lipoxin A4 levels, were sensitive to MK-886, displaying an anxiogenic-like state in response to treatment. Moreover, exogenous lipoxin A4 induced an anxiolytic-like profile in the EPM test. Our findings are in line with other reports showing no difference between FLAP KO or 5-LO KO and their control strains in adult mice, but increased anxiety-like behavior in aged mice. We also show for the first time that lipoxin A4 affects mouse behavior. In conclusion, we propose an age-dependent relevancy of endogenous 5-LO derivatives in the modulation of anxiety-like behavior, in addition to a potential for exogenous lipoxin A4 in producing an anxiolytic-like state.